A Community of Mourners: collective sentiment, national belonging and the Muslim 'Other' after the 'Sydney Siege'. Issue 3 (2nd July 2016) - Mikola, Maša; Colic-Peisker, Val; Dekker, Karien
ABSTRACT: This paper analyses collective sentiment in media responses to the event known as the 'Sydney Siege' (December 2014), focusing on the everyday narratives about nationhood and belonging. The aim of the article is to analyse how a hostage-taking situation, represented as a terrorist act, served to reinforce the boundaries of a national community in relation to Australian Muslims. The theoretical framework draws from Ahmed's ('The Organization of Hate', in Emotions: A Cultural Studies Reader, edited by J. Harding and E. D. Pribram, 251–267 (London and New York: Routledge, 2009)) concept of 'affective economies' and focuses on the inclusion/exclusion dynamic working through the lens of emotions. The paper analyses data collected from three high-circulation Australian daily newspapers ( The Sydney Morning Herald, The Australian and The Daily Telegraph) and one prime-time current affairs television program (ABC's 7.30 Report ), as well as government press releases . A qualitative thematic discourse analysis of 151 articles, mediated by NVivo software, provided insight into the ways in which collective sentiment was (trans)formative to narratives about nationhood, belonging and the Muslim 'Other'. We argue that the outpouring of collective sentiments of fear, compassion/solidarity and grief during the 'Sydney Siege' made the everyday experience of the Muslim presence in Australia visible in a public space as well as in the public debate.